2017
DOI: 10.1002/jcla.22201
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative method for the determination of bosutinib in human plasma using high‐performance liquid chromatography and ultraviolet detection

Abstract: The proposed HPLC-UV method was successfully applied as an assay to detect bosutinib in human plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…Good extraction recoveries (80.7%–98.5%) were obtained for the four TKIs. This study demonstrated a recovery rate (Table 3) similar to or higher than those reported in previous studies using similar SPE methods (recovery rates of 74%–76% for dasatinib, 20 72%–78% for nilotinib, 20 84%–85% for bosutinib, 25 and 78%–88% for ponatinib 19 ). Although the SPE pretreatment method was the same as the one used in previous studies, our use of 2% phosphoric acid as a dilution solvent for the serum samples may have contributed to the higher recovery rate.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Good extraction recoveries (80.7%–98.5%) were obtained for the four TKIs. This study demonstrated a recovery rate (Table 3) similar to or higher than those reported in previous studies using similar SPE methods (recovery rates of 74%–76% for dasatinib, 20 72%–78% for nilotinib, 20 84%–85% for bosutinib, 25 and 78%–88% for ponatinib 19 ). Although the SPE pretreatment method was the same as the one used in previous studies, our use of 2% phosphoric acid as a dilution solvent for the serum samples may have contributed to the higher recovery rate.…”
Section: Discussionsupporting
confidence: 86%
“…The accuracy and precision values for dasatinib (2–500 ng/ml) were within ±14.3% and 17.9%, nilotinib values (100–5000 ng/ml) were within ±14.4% and 7.3%, bosutinib values (10–500 ng/ml) were within ±12.8% and 7.3%, and ponatinib values (10–500 ng/ml) were within ±11.9% and 10.1%, respectively. On the other hand, the accuracy and precision values in the previous single analyte assays for dasatinib (10–1000 ng/ml) were within ±4.1% and 15.8%, 20 the values for nilotinib (10–5000 ng/ml) were within ±10.5% and 10.4%, 20 the values for bosutinib (25–1500 ng/ml) were within ±10.2% and 8.7%, 25 and the values for ponatinib (1–250 ng/ml) were within ±9.0% and 10.8%. 19 The simultaneous measurement of multiple drugs and concentration range of the calibration curves resulted in similar or higher accuracy and precision than previous assays; however, they all met the criteria of FDA's validation guideline.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations